Head and neck lymphedema after radiotherapy − Prevalence, changes and associated factors − a prospective observational cohort study - Hagren, A.; Sjövall, J.; Brogårdh, C.; Johansson, K.; Ekvall Hansson, E. (Oral Oncology, 2025)
Background: There is an increasing incidence of oropharyngeal squamous cell carcinoma (OPSCC) survivors living with treatment-related head and neck lymphedema (HNL). This study aimed to determine (i) the prevalence of external HNL, (ii) changes in HNL over a nine-month period post-treatment, and (iii) factors associated with HNL among patients with OPSCC treated with (chemo)radiotherapy. Methods and Results: Fifty patients were recruited (mean age 64 years), where two thirds were male. HNL was assessed with a lymph scanner in seven facial points, and with a measuring tape at three levels, before treatment, and three and nine months post-treatment. Paired sample t-test was used to calculate changes in HNL and logistic regression analysis identified factors associated with HNL, including age, gender, BMI, physical activity, addition of chemotherapy and radiation dose. At three months post-treatment, 80 % of patients had HNL, which decreased to 69 % nine months post-treatment. The submental point was the most common location for HNL and showed the greatest change over the nine-month period. Differences in circumferential measurements were small. Low physical activity increased the odds of developing HNL (p = 0.011). Conclusions: HNL is a common side effect after (chemo)radiotherapy treatment. The changes in HNL at the submental point seem to be greatest while the changes in neck circumferential are small. Since a low level of physical activity increased the risk of developing HNL, it may be important to encourage physical activity in this population.
Keywords: Body mass index; Cohort studies; Head and neck neoplasm; Lymphedema; Physical activity; Radiotherapy; Squamous cell carcinoma